Caring Ability of Postcaesarean Mothers and It's Association with Cultural Value - Atik Hodikoh; Setyowati Setyowati (Universitas Airlangga, 2015)
Introduction: Ability to care of  postcaesarean mother affected by multifactor; moternal  characteristic, knowledge and cultural values. Postcaesarean mother has high level of dependency in performing selfcare and baby care. The aim of this study was  to  identified  of selfcare and baby care and relation with that factors  and cultural behaviour associaated pospartum care. Method: this study used cross sectional design with a purpossive sampling of 66 post caesarean mother ini five hospital in West Java. Instrumen used consisted of  maternal  characteristic including ages, parity,job, income, knowledga,  cultural values, cultural behaviour  and observasional instruments of  the ability to care. Result: there was a significant relationship between job characteristic and cultural values with the ability to care, for the correlation r 0.295 an 0.355 (p value = 0.003). Discussion: nurses must perform a cultural approach in facilitating the mother to care for themselves and care for the baby in accordance with their cultural values, so that the mother can perform optimally care. Keywords: ability to, cultural values, job, postcaesarean care